Sedative Effectiveness of Essential Oils of Red Rose Flower (Rosa Damascena) and White Jasmine Flower (Jasminum Sambac) on Male Mice (Musculus) by Olfactory Aromatherapy - Nasruhan Arifianto; Cinthya Ratna Yuniar; Cikra Ikhda Nur H.,S; Arifah Yusrina; Fitria Nur Hidayati (Journal of Innovative and Creativity, 2025)
Insomia is a condition in which a person cannot sleep, often wakes up and has difficulty falling back asleep. Aromatherapy will provide a sense of calm when inhaled. Red rose and white jasmine aromatherapy contains linalool and geraniol substances that are beneficial for overcoming sleep disorders. The purpose of this study was to examine the sedative effects of red rose and white jasmine essential oils on mice. This study used an experimental method tested on male mice to test the sedative effect of red rose (Rosa damascena) and white jasmine (Jasminum sambac) oils on mice (Mus musculus) by means of aromatherapy (by inhalation) using the volume of red rose (Rosa damascena) and white jasmine (Jasminum sambac) essential oils for 4 hours with a stratified volume of 5 ml in 300 ml of solution,  10 ml in 300 ml of solution and 15 ml in 300 ml of solution. The data obtained from the results of the sedative effectiveness test of red rose oil on mice were statistically analyzed with the ANOVA one-way test. The results of the ANOVA oneway test showed that red rose essential oil and white jasmine had a sedative effect on mice at a level of 5 ml in 300 ml of solution and at a level of 10 ml in 300 ml of diffuser water solution while white jasmine essential oil volume of 15 ml in 300 ml of diffuser water with ANOVA test results of 0.000 < 0.05 with a positive control value of 43.33 minutes, negative control 13.00 minutes, 5ml oil 21.00 minutes, oil 10 ml 37.50 minutes, and 15 ml oil 67.67 minutes